Study on Supply-Demand Dynamics and Prospects of Maize and Soybean in China - Wang, Shengwei; Wang, Yu; Wu, Tianlong; Li, Ganqiong; Zhang, Yongen; Yu, Wen (Transactions on Economics, Business and Management Research, 2024)
Maize and soybean are important grain and oil crops in China. Being the first grain crop in China, maize is important feed and raw materials for industrial uses, while soybean constitutes the major raw materials for animal protein feed. Hence, both are essential and strategic agricultural products related to people’s livelihood worldwide. This paper mainly analyzed the changes in production, consumption, trade and price of maize and soybean in China, and applied the CAMES model to predict the trends in maize and soybean production, consumption, trade and price in the next decade (2024-2033) based on certain hypotheses of economic and social conditions and agricultural production conditions. According to the study, supply and demand of maize in China will witness regional balance in the foreseeable future, when maize imports will constantly decrease and the maize self-sufficiency rate will exceed 97%. In the meantime, imported soybeans will still be the major source for domestic feed use, with Brazil and the United States as the major importers. Despite the high imports, the self-sufficiency rate of soybean in China will keep rising and soybean imports will decrease due to the decline in feed processing and the increase in domestic soybean production capacity. In addition, this study also introduced the domestic and international uncertainties facing the supply and demand of maize and soybean in China in the future.